CO2‐Mediated H2 Storage‐Release with Nanostructured Catalysts: Recent Progresses, Challenges, and Perspectives. Issue 30 (3rd July 2019) - Asefa, Tewodros; Koh, Katherine; Yoon, Chang Won
Abstract: It has increasingly become clear that economic growth worldwide based on fossil fuel energy supply cannot be sustained; thus, alternative, renewable energy sources and carriers must be urgently developed to maintain growth. Dihydrogen (H2 ), which can produce energy without generating environmental pollutants, can play a major role in this endeavor. However, to use H2 in renewable energy systems, systems and materials that can store and transport it, or convert it into easier‐to‐handle/transport synthetic fuels, need to be developed. In this article, first, many of the issues related to both homogeneous and heterogeneous catalysts that are being developed to help H2 's use as energy carrier are discussed. More focus is then given to heterogeneous nanocatalysts that are developed for reversible CO2 ‐mediated hydrogenation and dehydrogenation reactions involving chemical hydrogen carriers and delivery systems, mainly formic acid/CO2 and formate/bicarbonate. The challenges associated with the development of nanocatalysts based on earth‐abundant elements for dehydrogenation and hydrogenation reactions of these compounds for H2 storage and release are emphasized in the discussions. Finally, the pressing research questions and major issues that need to be addressed in the near future to help the realization of the "hydrogen economy" are outlined. Abstract : There has recently been an increased interest in various renewable energy carriers and systems, including H2 . This article discusses heterogeneous and nanostructured catalysts that have been investigated for dehydrogenation and hydrogenation reactions involving formic acid/CO2 and formate/bicarbonate to store and transport H2 . A perspective on what the future may hold for this field is also included.